An effective teacher as an extremely good classroom manager in an EFL class - Hernández León, Sobeida Iliana; Recinos López, Joselyn Jael; Llanes Márquez López, Jorge Homero; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2012)
The present research will be based on a factual report and will be taken from different bibliographic resources. Since the importance that an ESL class has in a school in order to learn English as a foreign language, it is considered that the classroom management is a fundamental aspect that teachers must take into account to have a successful learning process. In order to have an effective classroom management, the teacher must take into account some important points that will assure the success in teaching the new language. For example, the teacher should know the curriculum, in which the language will be taught, the procedures that the teachers have to follow before they plan a class, the classroom rules that students have to follow in order to be in a class, and the environment that the teacher wants to have to encourage students to study the language. Another important point that must be taken into account is how to become an affective teacher in an EFL classroom and, finally, the material used in class.
Anexos.
Tesis -- (Licenciatura en Idioma Inglés, opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2012
Referencias hoja 24
Keywords: Lenguaje y lenguas -- Enseñanza; Adquisición de segundo lenguaje; Métodos de enseñanza